ANALISIS PERAN GURU DALAM MENERAPKAN KARAKTER TANGGUNG JAWAB PESERTA DIDIK PADA PEMBELAJARAN SOSIOLOGI KELAS X7 DI SMA NEGERI 1 SUNGAI AMBAWANG KABUPATEN KUBU - Yuliana, Yusi; Ramadhan, Iwan (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2025)
The character trait of responsibility has been taught to students in class X7 at SMA Negeri 1 Sungai Ambawang, Kubu Raya Regency, but in its application in the classroom, the attitude of responsibility among class X7 students has not yet been optimally formed. Considering that in the learning process, teachers do not only have the role of teaching knowledge, but teachers have various roles in the learning process. Therefore, this study aims to analyze the role of teachers as instructors, educators, and motivators in instilling a sense of responsibility in students in the 10th grade sociology class at SMA Negeri 1 Sungai Ambawang in Kubu Raya Regency. This research was conducted at SMA Negeri 1 Sungai Ambawang, Kubu Raya Regency. The objects in this study were Sociology teachers and Grade X7 students, with a total of 36 students. The results of the study indicate that the role of teachers as educators in instilling a sense of responsibility in students is to assign group tasks, set deadlines for completing the tasks, and create a classroom atmosphere that supports the development of responsibility in students in completing their tasks. The role of teachers as educators in instilling responsibility is to assist students while they are working on assignments and provide guidance to students in completing their assignments. The role of teachers as motivators in instilling responsibility is to encourage students to take responsibility for their assignments and build their self-confidence.The abstract contains a brief description of the research problem and objectives, the methods used, the urgency of the research, teaching, learning or management of the educational unit and the presentation of the research results. The abstract should reflect the content of the article. The abstract must be written in a paragraph of a maximum of 300 words. Keywords should be included to describe the problem area, and the terms underlying the conduct of the research. Keywords can be single words or combinations of words (phrases). The number of keywords is usually between 3 - 5 words. Keywords are needed for computerization. Searching for research titles and abstracts is easy with these keywords.